Metabolic dysfunction in a rat model of early‐life scarcity–adversity: Modulatory role of cafeteria diet. Issue 11 (8th October 2018) - Sagae, Sara C.; Zanardini, Bárbara; Ribeiro‐Paz, Edson D.; Amaral, Ana Claudia; Bronczek, Gabriela A.; Lubaczeuski, Camila; Grassiolli, Sabrina; Koehler‐Santos, Patrícia; de Oliveira, Jarbas Rodrigues; Donadio, Márcio Vinícius Fagundes; Raineki, Charlis
Abstract : New Findings: What is the central question of this study? Early‐life adversity is associated with increased risk for obesity and metabolic dysfunction. However, it is unclear whether obesity and metabolic dysfunction result from coping strategies to deal with adversity‐related emotional dysregulation, a direct programming of systems regulating metabolic function, or a combination of both. What is the main finding and its importance? Early‐life adversity increases vulnerability to later‐life obesity and metabolic dysfunction, indicating that genetics and adult lifestyle are not the only determinants of obesity and related metabolic dysfunction. Moreover, consumption of cafeteria diet exacerbated metabolic dysfunction associated with early‐life adversity, suggesting that poor dietary choices might have a bigger impact in the context of early‐life adversity. Abstract: Early‐life adversity has become recognized as an important factor contributing to adult obesity and associated metabolic dysfunction. However, it is unclear whether obesity and metabolic dysfunction associated with early‐life adversity result from coping strategies to deal with adversity‐related emotional dysregulation, a direct programming of systems regulating metabolic function, or a combination. Interestingly, both early‐life adversity and later‐life dietary choices affect immune function, favouring pro‐inflammatory mechanisms that are associated with obesity‐related metabolic dysfunction. To investigate the unique and/or interactive effects of early‐life adversity and later‐life dietary choices for increased vulnerability to obesity and metabolic dysfunction, and specifically the role of the immune system in this vulnerability, we combined a naturalistic rat model of early‐life scarcity–adversity with a rat model of obesity, the cafeteria diet. Our results indicate that early‐life adversity alone induces insulin resistance, reduces pancreatic insulin secretion, plasma concentrations of triglycerides and cholesterol, and increases fasting glucose and tumour necrosis factor‐α plasma concentrations. Importantly, animals exposed to adverse rearing were more vulnerable to metabolic dysregulation associated with the cafeteria diet, given that they consumed more energy, showed more severe hepatic steatosis and increased concentrations of the pro‐inflammatory cytokine interleukin‐1β than normally reared animals fed the cafeteria diet. Together, our results suggest that early‐life adversity negatively programmes physiological systems that regulate metabolic function and increases vulnerability to obesity and metabolic dysfunction in adulthood. These results highlight the intrinsic relationship between the quality of the early postnatal environment and later‐life dietary choices on adult health outcomes. Abstract :